2008
DOI: 10.1038/ijo.2008.226
|View full text |Cite
|
Sign up to set email alerts
|

Daylong pituitary hormones in morbid obesity: effects of bariatric surgery

Abstract: Moderate obesity is known to be associated with multiple endocrine abnormalities. Less information is available on the hormonal status of patients with morbid obesity and on the effects of major weight loss. We studied 16 severely obese (BMI 40.6-69.9 kg/m 2 ) nondiabetic patients and 7 nonobese (BMI range 24.6-27.7 kg/m 2 ), sex-and age-matched healthy volunteers. During 24 h in a metabolic ward, four meals were administered and hourly blood samples were drawn from a central venous catheter for the measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 61 publications
0
28
1
1
Order By: Relevance
“…This may be one of the factors that she is maintaining her normal glycemia and lipid profiles despite her continued obesity. Though an increase in TSH levels has been reported in the morbidly obese (43), the levels of TSH, fT3 and fT4 in the present case were in normal range and did not change postoperatively.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…This may be one of the factors that she is maintaining her normal glycemia and lipid profiles despite her continued obesity. Though an increase in TSH levels has been reported in the morbidly obese (43), the levels of TSH, fT3 and fT4 in the present case were in normal range and did not change postoperatively.…”
Section: Discussioncontrasting
confidence: 77%
“…Growth hormone (GH) secretion is influenced by body composition, and in patients with obesity, GH production peaks are few and suppressed (43)(44)(45). Also, it has been reported that GH is stimulated by ghrelin (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…In morbidly obese patients with subclinical hypothyroidism, bariatric surgery led to changes in obesity-related adipokines believed to influence the synthesis and secretion of thyroid hormones. 9,19 However, in a recent study from our laboratory, 10 the direct relationship between 24-h mean concentrations of TSH and leptin in euthyroid obese patients was lost after adjusting for fat mass, suggesting that other mechanisms modulate TSH concentrations in morbidly obese patients. Another explanation is that the thyroid hormone profile of the obese individuals reflects pituitary resistance to thyroid hormones, with a variable degree of secondary impairment of thyroid hormone peripheral metabolism.…”
Section: Discussionmentioning
confidence: 86%
“…On the other hand, this study is one of the few investigations that have unequivocally shown that weight loss leads to a reduction in both TSH and FT 3 levels. 9,10,19,20 Several explanations have been proposed to account for the influence of obesity on thyroid hormones. One suggests that the increased TSH level could reflect pituitary adaptation to increased adiposity through adipokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation